Using acupuncture in complex treatment of chronic apical periodontitis (LLC "Endo Press", 2020)
In recent decades, the most important problem in clinical medicine and, in particular, the practice of dentistry, is to find ways and methods to improve the resistance of the organism, the maintenance of homeostasis at the physiological level. One of these methods is acupuncture, currently receiving increasing recognition. Mechanisms to ensure that the therapeutic effect of acupuncture to date remains understudied. In this paper, we studied 120 patients with chronic apical periodontitis. Patients were studying the functional state of the autonomic nervous system via metered electrophoresis adrenaline and carbachol in the skin of the forearm as described in the modification A.V. Loginova, A.F. Zharkin and test dermographism. For acupuncture diagnosis method was used in the modification E. Nakatani (Riodoraku) A.I. Nechushkina. The findings suggest the possibility of immune and prevention of immunosuppressive state with the help of acupuncture in the treatment of patients with chronic apical periodontitis. This method is technically simple, harmless, economically efficient, no complications, in contrast to drug therapy and physical therapy. All this makes it advisable to include acupuncture in the range of therapeutic interventions in chronic periodontitis.